2019
DOI: 10.1111/obr.12817
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity in pregnancy impacts offspring cardiometabolic health: Systematic review and meta‐analysis of animal studies

Abstract: SummaryObesity before and during pregnancy leads to reduced offspring cardiometabolic health. Here, we systematically reviewed animal experimental evidence of maternal obesity before and during pregnancy and offspring anthropometry and cardiometabolic health. We systematically searched Embase and Medline from inception until January 2018. Eligible publications compared offspring of mothers with obesity to mothers with a normal weight. We performed meta‐analyses and subgroup analyses. We also examined methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 105 publications
(197 reference statements)
2
44
0
1
Order By: Relevance
“…Resting pulse rate in children has also been reported to be inversely related to physical activity, 33 but this is an unlikely explanation for the difference in pulse rates observed between intervention arms in this study, as there was no association with parent‐reported child activity and sedentary time and resting pulse rate. An association between maternal obesity and offspring cardiometabolic dysfunction is widely reported in experimental animals 13‐16,34 . Rodent maternal obesity has been related to a sustained increase in offspring central sympathetic activity at the level of the hypothalamic neuronal pathways involved in peripheral autonomic regulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resting pulse rate in children has also been reported to be inversely related to physical activity, 33 but this is an unlikely explanation for the difference in pulse rates observed between intervention arms in this study, as there was no association with parent‐reported child activity and sedentary time and resting pulse rate. An association between maternal obesity and offspring cardiometabolic dysfunction is widely reported in experimental animals 13‐16,34 . Rodent maternal obesity has been related to a sustained increase in offspring central sympathetic activity at the level of the hypothalamic neuronal pathways involved in peripheral autonomic regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many reports of the consequences of maternal obesity on offspring health from animal 15 and cohort studies 7 very few have addressed the influence of an antenatal intervention beyond infancy 21 . The only study of an antenatal diet and physical activity intervention in women with obesity, which was effective at reducing GWG, reported no effect on offspring body composition at 2.8 years of age (n = 254) 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, outcomes from this study are clinically relevant to 2/3 of women entering the reproductive age as overweight or obese without diabetes, in the United States [ 37 , 38 ]. This population is overrepresented in obstetrics and is understudied [ 2 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Careful breeding structures need to be employed as diet and age of the breeders can have an impact on subsequent generations [53][54][55]. Obesity in dams can affect the metabolic status of their offspring [56,57] and the age of breeding males can have effects on behavioural phenotypes in the offspring [58]. It is also essential that both sexes are studied as there are clear differences in the effects of interventions and the effects of ageing.…”
Section: Strain/model and Breeding Designmentioning
confidence: 99%